2017
DOI: 10.1038/s41598-017-08302-5
|View full text |Cite
|
Sign up to set email alerts
|

Strong, Ductile, and Thermally Stable bcc-Mg Nanolaminates

Abstract: Magnesium has attracted attention worldwide because it is the lightest structural metal. However, a high strength-to-weight ratio remains its only attribute, since an intrinsic lack of strength, ductility and low melting temperature severely restricts practical applications of Mg. Through interface strains, the crystal structure of Mg can be transformed and stabilized from a simple hexagonal (hexagonal close packed hcp) to body center cubic (bcc) crystal structure at ambient pressures. We demonstrate that when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 52 publications
0
22
1
Order By: Relevance
“…have shown that the bcc‐Mg structure may appear in Mg/Nb multilayers under ambient conditions. Pathak et al . have demonstrated that in 5 nm/5 nm Mg/Nb multilayers both phases adopted the same bcc lattice parameter < a >=0.3347 nm, whereas in 50 nm/50 nm multilayers the lattice parameters of Mg and Nb layers are similar to those of bulk.…”
Section: Theoretical Approach To Destabilization Of Hydrogen‐storage mentioning
confidence: 99%
“…have shown that the bcc‐Mg structure may appear in Mg/Nb multilayers under ambient conditions. Pathak et al . have demonstrated that in 5 nm/5 nm Mg/Nb multilayers both phases adopted the same bcc lattice parameter < a >=0.3347 nm, whereas in 50 nm/50 nm multilayers the lattice parameters of Mg and Nb layers are similar to those of bulk.…”
Section: Theoretical Approach To Destabilization Of Hydrogen‐storage mentioning
confidence: 99%
“…The mechanical strength inferred from indentation hardness can be as high as 0.8 GPa when the layers are a few nanometers thick. 32 Pathak et al 33 also demonstrated an extremely high peak strength of 1.7 GPa of Mg/Nb multilayers with an individual layer thickness of 50 nm by micro-pillar compression.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, the length scale dependent the fracture toughness of fcc/hcp NMMFS is also influenced by the transformation of lattice structures [15]. Due to the dimension induced phase transformation in Ru layer, the fcc/fcc Cu/Ru should possess a great deal of slip systems to accommodate plastic deformation; while, hcp Ru are difficult to deform due to few slip systems are available [21,115,116]. Accordingly, the difference in fracture toughness between fcc/hcp multilayers whether has structure transformation are summarized, as shown in Figure 17.…”
Section: Phase Transformation Enhanced Tougheningmentioning
confidence: 99%